A SURVEY STUDY: THE MEASUREMENT OF EFL STUDENTS’ READING ENGAGEMENT - Evi Puspitasari; Noor Maulida Hayati (STKIP Siliwangi, 2023)
Reading engagement combines motivation, interests, attitudes, emotions, self-regulation, and gaining a flow state while reading. The study's objective is to analyze the reading engagement level of English as a Foreign Language (EFL) students at one of the private universities in Yogyakarta. This survey study was taken place by distributing a questionnaire to collect the data. A questionnaire comprising three constructs indicating reading engagement, namely construct of task value, anxiety, and flow, was distributed to 149 students online to measure the reading engagement level. After the data were gained and analyzed, it was known that their engagement level in reading was moderate, and the factor with the highest mean score was task value. The results implied that students' enjoyment of reading English texts is not disappointing but still needs improvement. Thus, strategies should be applied to make students more in the zone with reading which will lead to their excellent academic achievement.